Epiphytic microbiota source stimulates the fermentation profile and bacterial community of alfalfa-corn mixed silage - Tang, Xiaolong; Liao, Chaosheng; Huang, Xiaokang; Chen, Cheng; Xu, Duhan; Chen, Chao (Frontiers in Microbiology, 2024)
The epiphytic microbiota source on plants plays a crucial role in the production of high-quality silage. To gain a better understanding of its contribution, the microbiota of alfalfa (M1C0), corn (M0C1) and the resulting mixture (M1C1) was applied in alfalfa-corn mixed silage production system. M1C0 decreased ammonia-N levels in terms of total nitrogen (57.59-118.23 g/Kg TN) and pH (3.59-4.40) values (P<0.01), which increased lactic acid (33.73-61.89 g/Kg DM) content (P<0.01). Consequently, this resulted in higher residual water-soluble carbohydrate (29.13-41.76 g/Kg DM) and crude protein (152.54-167.91 g/Kg DM) contents, as well as lower NDF (427.27 g/Kg DM) and ADF (269.53 g/Kg DM) contents in the silage compared to M1C1-and M0C1-treated samples. Moreover, M1C0 silage showed significantly higher bacterial alpha diversity indices (P<0.05), including the number of observed species and Chao1 and Shannon diversity indices, at the later stages of ensiling. Lactobacillus, Kosakonia and Enterobacter were the dominant bacterial species in silages, with a relative abundance of >80%. However, the abundance of Lactobacillus amylovorus in M0C1-and M1C1-treated silage increased (P<0.01) in the late stages of ensiling.These findings confirmed that the epiphytic microbiota source exerts competitive effects during anaerobic storage of alfalfa-corn mixed silage.